Diagnosis of bullying in targeted schools in the municipality of Santa Ana (Educational Knowledge, 2019)
This article presents a diagnostic study conducted in a sample of targeted schools in the municipality of Santa Ana as input for the Art, Culture, Recreation, Sports, and Citizenship Unit of the Ministry of Education, Science, and Technology (MINEDUCYT).The descriptive research covered nine of the thirty targeted schools, totaling 117 participants, including administrators, teachers, and students. Bullying is not a new phenomenon; in most cases, its existence is assumed. Unfortunately, however, there is a lack of a theoretical and practical framework that explains how it develops, hindering effective intervention and gradual eradication. For this reason, the manifestations of this problem are described, and the mechanisms outlined in the School Code of Conduct for addressing it are identified.This process, due to its sensitive and socio-educational nature, revealed diverse perspectives: on the one hand, the administrators' fear of viewing the phenomenon as an administrative shortcoming rather than a social problem requiring appropriate intervention for the benefit of the entire educational community; and on the other hand, optimism among teachers and students, as it brought to light a problem affecting everyone. All of this contributed to the development of a research resource that will inform future strategies for addressing bullying promptly, precisely, and effectively.
Keywords: Bullying; school coexistence; selected schools; procedures for conflict resolution